Unique allosteric effect-driven rapid adsorption of carbon dioxide in a newly designed ionogel [P4444][2-Op]@MCM-41 with excellent cyclic stability and loading-dependent capacity. Issue 14 (16th March 2017) - Xue, Chunfeng; Zhu, Hongye; Du, Xiao; An, Xiaowei; Wang, Enyang; Duan, Donghong; Shi, Lijuan; Hao, Xiaogang; Xiao, Bo; Peng, Changjun
Abstract : Allosteric effect-driven rapid stepwise CO2 adsorption of pyridine-containing anion functionalized ionic liquid [P4444 ][2-Op] confined into mesoporous silica MCM-41. Abstract : To achieve low cost, high rate and attractive capacity of CO2 adsorption by using ionic liquids (IL), a new mesostructured ionogel, pyridine-containing anion functionalized IL tetrabutylphosphonium 2-hydroxypyridine ([P4444 ][2-Op]) encapsulated silica MCM-41 (noted as PM-w), is fabricated by loading the IL [P4444 ][2-Op] with multiple active sites into porous silica MCM-41 through a simple moisture-controlled impregnation–evaporation method. Allosteric effect driven gas sorption on the electronegative oxygen and nitrogen atoms of the nanoconfined IL [P4444 ][2-Op] makes it take no more than 2 min for the ionogel PM-5 to achieve the 90% of saturated adsorption capacity. The corresponding adsorption rate is 30 times faster than that of the bulk IL. The ionogel PM-5 with the low IL loading of 5.0% shows the highest CO2 adsorption capacity up to 1.21 mmol (g-ionogel) −1 (14.89 mmol (g-IL) −1 ) at 50 °C in a gas mixture with N2, which is 9.25 times higher than that of the pure IL. Its excellent cyclic stability of more than 96% of the initial CO2 uptake repeatedly displayed after performing 10 cycles of adsorption–desorption tests. The enhanced thermal stability up to 450 °C in N2 is observed for the low loading ionogels since the strong interfacial layering of the IL prefers to dot the silica nanopores as monomolecular islands. Reversely, the high loading IL may aggregate into nanosized clusters that recover the poor thermal stability of the bulk IL. Reasonable decreases in their surface area, pore volume and pore size are observed with the IL loading up to 45%. They still exhibit highly ordered hexagonal mesostructures. The features of low loading and cost, rapid adsorption, high capacity and excellent cyclic stability make the ionogel PM-5 a competitive candidate in CO2 capture from flue gas.